(untitled) (BIBECHANA, 2023)
Snow avalanches present the major natural hazard in Himalayan region of Nepal. The loss of human life is the main effect of avalanche. The records and casualties compared with specific Europe countries which help to analyze the hazard in the mountain region and can be recommend to the public people of this area about the avalanche condition, prevention from it and dissemination of information. On analyzing the statistics of avalanche fatality in the high mountain of Asia from 1895 to 2022, the fatality number was 59 at Annapurna and Dhaulagiri mountain Peaks. Different highest peaks of mountains attract tourist and the massive amount of snow create an avalanche in these areas, so Avalanche is one of the most devastating hazards in Western Himalayan. This fatality events, and fatality rates of Nepal and Europe countries from 1971 to 2022 analyzes the collected data from the DesInventar data-set, Disaster Risk Reduction Portal of the government of Nepal. The European Avalanche Warning System is used in the government of Europe using the geographic Information system (ArcGIS) tools. This study recommends the establishment of an Avalanche warning System with proper tools in the western Himalayan to save the life of humans and property.